Technical analysis : relationship between price change and trading volume in the Singapore equity market - Lee, Chui Leng (2015)
This project focuses on the empirical studies of the relationship between volume traded with security price changes. It specially explores three areas. The contemporaneous relationship between trading volume and absolute price changes. Secondly, trading volume and price changes are asymmetric in equity markets (trading volume is greater when price ticks up than on price downticks). Finally, the contemporaneous relationship between trading volume and price changes per se. A sectoral breakdown analysis of the three relationships is also attempted. In the past, most academic research in the area of price-volume relationship were concentrated on the US markets with an exception of some studies based on the Hong Kong securities market. Hence, this project attempts to extend it to give a local context by focusing on the Singapore Equity market. This project covers a span of four years from 1987 to 1991 which is separated into two periods. Period 1 is from 1 July 1987 to 30 June 1988 and Period 2 is from 1 July 1990 to 30 June 1991. The study uses weekly data for twenty-three representative stocks chosen from the various sectors of the economy (namely industrial, hotel, finance and property). The results of this studies show a positive correlation between absolute price-changes and trading volume. Findings also suggest that there is no conclusive evidence on the existence of any relationship between trading volume and price change per se. The asymmetrical relationship between price and volume is also not supported.